Improvement of Pain Management by Nefopam in a Rat Adjuvant-Induced Arthritis Model - Dalix, Elisa; Maalouf, Mathieu; Linossier, Marie-Thérèse; Vanden-Bossche, Arnaud; Peyroche, Sylvie; Marotte, Hubert (Frontiers in Veterinary Science, 2022)
Introduction. The adjuvant-induced arthritis (AIA) model is widely used in research to investigate arthritis pathogenesis. Hind paw inflammation is the main outcome in this model with high loss of function partly related to pain. However, analgesics including non-steroidal anti-inflammatory drugs or opioid drugs interfere with inflammation process reducing their used. Therefore, we aimed to test nefopam, as a different acting molecule effect on arthritis development in order to improve pain management in the AIA model. Methods. Female Lewis rat were randomly divided in two groups and received an injection of Mycobacterium butyricum defining day (D) 0. At D6, rats (n=10) received nefopam (intraperitoneal or orally) or NaCl 0.9% IP or 1% sucrose in water (n=5 for each). Rats were monitored with arthritic index (AI) and ankle circumference. Pain was assessed by a scoring based on behavioural indicators. Histology, RT-qPCR, and microcomputed tomography were performed. Results. The clinical parameter AI and ankle circumference were not different in both groups at the various time points. However, pain score was significantly lower in nefopam group at early stage of disease. At a later stage of disease, inflammation was mildly lower whereas bone erosion and bone loss parameters trend to increase in hind paws from nefopam group. Conclusion. Nefopam provided a slight reduction of level on pain at the time of arthritis without reducing arthritis severity and bone loss in the rat AIA model. However, it should be administrated orally for a shorter period to avoid inflammation reduction in the long run.